Exploring Management and Effectiveness of Distribution of Infaq and Shadaqah Funds - Aminudin Ma'ruf; Novitasari, Ossa; Lathifah, Annisa Ul (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2024)
Infaq and Shadaqah emerge as pivotal elements of Islamic social finance. Both contribute to alleviating poverty and supporting the prosperity of society. This study explores the management and effectiveness of the management and effectiveness of the distribution of infaq and shadaqah funds, with case studies of LAZNAS Nurul Hayat and Yatim Mandiri. The paper adopts a qualitative research method with a descriptive analysis approach. The data in this study was obtained from interviews with the officers from both institutions and data collection from their official websites. The results of the study found that there are some similarities and differences between the institutions such as collection through CSR programmes and distribution of the funds through da’wah. The effectiveness of Nurul Hayat's LAZNAS in 2019 was categorized as very effective, while in 2020 the Gross Allocation to Collection Ratio and Gross Allocation to Non-Amil Ratio were categorized as less effective and ineffective. Differently, LAZNAS Yatim Mandiri Solo 2019-2020 Gross Allocation to Collection and Gross Allocation to Collection Non-Amil are categorized as ineffective, while in 2019-2020 Net Allocation to Collection Ratio and Net Allocation to Collection Ratio Non-Amil are categorized as effective and very effective. The study carries some limitations with a number of future recommendations.